The effect of sulfur-containing compounds on stress resistance of Drosophila melanogaster - Chaka, O.; Yanko, R.; Safonov, S.; Kolomiets, I.; Levashov, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
We have studied the resistance of D. melanogaster imago, Oregon-R stock, reared on the culture medium, supplied either with methionine (1 mg/ml), or with sodium thiosulphate (0.05 mol/l or 0.1 mol/l), to heat (thermal) and alimentary stress. Also we have analyzed the effect of these substances addition to the medium on fertility and pupa lethality of D. melanogaster. A significant increase of resistance to heat stress was shown in flies reared on the culture medium supplied with methionine. Percent of individuals survived after heat stress increased by 35.5%. Imago survival, in the conditions of alimentary deprivation, increased; in this group average life span increased for 3.7 hours, maximal – for 7.5 hours. Fertility of drosophila reared on the medium with addition of methionine increased; number of pupas obtained from one female was more, than in control by 44%. Pupa lethality in this group decreased in three times. Resistance to heat stress of flies reared on the medium with addition of sodium thiosulphate (0.05 mol/l) increased. Number of individuals survived after heat stress was more, than in control by 10%. However, resistance to alimentary deprivation decreased. Their average life span was less for 3.2 hour, than in the control group, and maximal life span was less for 5.4 hour. Resistance to heat stress of flies reared on the medium supplemented with 0.1 mol/l sodium thiosulphate decreased. Percent of individuals survived after heat stress was twice less. Average life span and maximal life span in the conditions of alimentary deprivation increased by 3.4 hours and by 5.5 hours respectively. Fertility of flies developed in the medium with sodium thiosulfate (0.05 mol/l) supplement increased by 48 %, while same index for those consumed sodium thiosulfate 0.1 mol/l had a clear tendency to reduction by 33%. Pupa lethality in both groups consumed sodium thiosulphate (0.05 mol/l and 0.1 mol/l) decreased by 28% and 35% respectively. Thus, methionine consumption by larvae of D. melanogaster promotes resistance to stress and fertility of Oregon-R stock. The effect of sodium thiosulphate on drosophila fitness indexes studied depends on its concentration in the culture medium.